Povratna veljava pravnih aktov s poudarkom na novejši ustavnosodni presoji - Mežnar, Tina (Pravni letopis, 2025)
In principle, the Constitution does not permit the retroactive effect of legal acts. Only in exceptional cases, subject to constitutionally determined criteria, can such retroactivity be consistent with the Constitution. The purpose of this article is to present the criteria applied by the Constitutional Court when assessing whether general legal acts with retroactive ef- fect comply with this constitutional exception. The first part, drawing from the case law of the Constitutional Court, outlines the distinction between true and quasi retroactivity. The second part sets out the criteria considered by the Constitutional Court when determining whether a general legal act with retroactive effect is exceptionally constitutionally permissible. Since, in cases where a legislative measure falls within an area also regulated by European Union law, the criteria for permissible retroactivity established in the case law of the Court of Justice of the European Union must also be met, these criteria are presented as well.
Keywords: case law of the Constitutional Court; Constitution; criteria for constitutionally permissible retroactivity; merila za ustavno dopustnost povratne veljave pravnih aktov; prava in neprava retroaktivnost; prepoved retroaktivnosti; prohibition of retroactivity; true and quasi retroactivity; Ustava; Ustava, prepoved retroaktivnosti, prava in neprava retroaktivnost, merila za ustavno dopustnost povratne veljave pravnih aktov, ustavnosodna presoja.